Sorprendente Perú : colección fotográfica de un país extraordinario - Macchione, Ezio (Colección Expresiones artísticas. Tema Comunicaciones., 2019)
The book comprises the photographic collection of Ezio Macchione (b. Italy, lives and works in Peru) that brings together 72 amazing images -most of them of vertical forma- about landscapes and unexplored nature in the jungle, mountains and coast of Peru, where the focus, interpretation and selection of photographs differ from the traditional iconography with which it is represented Peru.